PEDAGOGICAL PRACTICE IN THEATER IN PRI- SON: REPORT OF AN EPISTEMOLOGICAL TUR- NOVER (Revista NUPEART, 2023)
This text is a mixture of experience reports and academic reflections on the process of implantation of the Theater in the State School São José in Macapá (AP) located inside the Institute of Penitentiary Administration (IAPEN) from an extension rese- arch action of the Course of Theater of the Federal University of Amapá (UNIFAP). Between invisibilities and approximations, we present a process of reassessment of the pedagogical practice in Theater, promoting an epistemological turn in the methodo- logies of Theater-Education from the voices of all interlocutors participating in the project in a personal/conceptual dialogue about the formative processes present in Theater actions in Communities.
Keywords: Theater; Prison; Teaching-Learning